159k views
3 votes
Solve the equation
(3 y^(4)-5 x^(2) y^(2) -6 x^(4) ) dx-(4x y^(3)) dy=0 leaving your answer in implicit form.

1 Answer

3 votes

(3y^4-5x^2y^2-6x^4)\,\mathrm dx-4xy^3\,\mathrm dy=0\iff(\mathrm dy)/(\mathrm dx)=(3y^4-5x^2y^2-6x^4)/(4xy^3)

Multiplying both the numerator and denominator by
\frac1{x^4}, we get


(\mathrm dy)/(\mathrm dx)=(4\left(\frac yx\right)^4-5\left(\frac yx\right)^2-6)/(4\left(\frac yx\right)^3)

Since the derivative can be expressed as a function of
\frac yx, the ODE is homogeneous. This means substituting
y=xv will be an effective approach. Indeed, we have
(\mathrm dy)/(\mathrm dx)=x(\mathrm dv)/(\mathrm dx)+v, and the ODE can be rewritten as the separable equation


x(\mathrm dv)/(\mathrm dx)+v=(3v^4-5v^2-6)/(4v^3)

x(\mathrm dv)/(\mathrm dx)=-(v^4+5v^2+6)/(4v^3)

(4v^3)/(v^4+5v^2+6)\,\mathrm dv=-\frac{\mathrm dx}x

\displaystyle\int(4v^3)/(v^4+5v^2+6)\,\mathrm dv=-\int\frac{\mathrm dx}x

\displaystyle\int\left((12v)/(v^2+3)-(8v)/(v^2+2)\right)\,\mathrm dv=-\ln|x|+C

6\ln(v^2+3)-4\ln(v^2+2)=-\ln|x|+C

\ln((v^2+3)^6)/((v^2+2)^4)=-\ln x+C

((v^2+3)^6)/((v^2+2)^4)=\frac Cx


(\left((y^2)/(x^2)+3\right)^6)/(\left((y^2)/(x^2)+2\right)^4)=\frac Cx

((y^2+3x^2)^6)/(x^4(y^2+2x^2)^4)=\frac Cx

((y^2+3x^2)^6)/((y^2+2x^2)^4)=Cx^3

You're welcome to unpack this further, but I would stop here.
User Cherese
by
6.0k points